2004
DOI: 10.1038/sj.jhh.1001773
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic changes in patients with malignant phase hypertension: The West Birmingham Malignant Hypertension Register

Abstract: In order to study the echocardiographic abnormalities in consecutive patients with malignant phase hypertension (MHT), we reviewed echocardiograms of 31 patients (23 male; mean age 52714 years) with MHT who were admitted to our unit. Trans-thoracic echocardiography was carried out in all patients, and echocardiographic measurements were compared with those of 39 patients (30 male; mean age 54710 years) with controlled nonmalignant essential hypertension, and 32 (19 male; mean age 51710 years) healthy normotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
6
1
2
Order By: Relevance
“…In our case significant LVH exceeded values reported in patients with malignant hypertension (LV mass height À 2.7 À 126 g m À 2.7 vs mean 78 g m À 2.7 in the report by Gosse et al 6 and LV mass/ index 685 g/340 g m À 2 vs mean 357 g/192 g m À 2 in the report by Nadar et al 5 ). It can be speculated that in our patient both elevated BP and detrimental effect of excessive amounts of aldosterone on the heart and vasculature might independently contribute to the development of marked LVH.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…In our case significant LVH exceeded values reported in patients with malignant hypertension (LV mass height À 2.7 À 126 g m À 2.7 vs mean 78 g m À 2.7 in the report by Gosse et al 6 and LV mass/ index 685 g/340 g m À 2 vs mean 357 g/192 g m À 2 in the report by Nadar et al 5 ). It can be speculated that in our patient both elevated BP and detrimental effect of excessive amounts of aldosterone on the heart and vasculature might independently contribute to the development of marked LVH.…”
contrasting
confidence: 57%
“…Nadar et al 5 showed that patients with malignant hypertension had significant LVH in association with systolic dysfunction irrespectively of the duration of known hypertension. Also Gosse et al 6 documented in 46 patients with malignant hypertension that at baseline they were characterized by important LVH and alteration in systolic function.…”
mentioning
confidence: 99%
“…4 Taken together, in the absence of definite evidence, clinicians must continue to administer these studies have had major limitations, such as a short follow-up duration and the lack of use of 3-dimensional echocardiography. [41][42][43] LVH, observed in patients with new-onset MHT, may at least partly reflect an adaptive response to persistently elevated BP, and its presence is associated with unfavorable prognosis. Indeed, the duration of the follow-up and the quality of BP control had a strong direct effect on prognosis in patients with MHT presenting with LVH.…”
Section: Identifiable Causes Of Malignant Hypertensionmentioning
confidence: 99%
“…Heightened public awareness and screening of the population are necessary to detect hypertension early enough so it can be treated before critical organs are damaged. Lifestyle adjustments in diet and exercise and compliance with medication regimes are important factors in determining the outcome for people with hypertension 5,6 . Several classes of anti-hypertensive medications are available, including ACE inhibitors, ARB drugs, betablockers, diuretics, calcium channel blockers, alpha-blockers, and peripheral vasodilators.…”
Section: Introductionmentioning
confidence: 99%